Disseminated Talaromyces marneffei and Mycobacterium intracellulare coinfection in an HIV-infected patient. (September 2015) - Seok, Hyeri; Ko, Jae-Hoon; Shin, Inseub; Eun, Young Hee; Lee, Seung-Eun; Lee, You-Bin; Peck, Kyong Ran
Highlights: Talaromyces marneffei is an opportunistic pathogen in immunocompromised hosts. Coinfection of T. marneffei with another opportunistic pathogen is rarely reported. We report the first case of T. marneffei and M. intracellulare coinfection in an AIDS patient. Abstract: A 25-year-old man with human immunodeficiency virus (HIV) infection presented with fever that had lasted 1 month. The CD4+ T lymphocyte count was 7 cells/μL and computed tomography showed several small lung nodules, splenomegaly, and multiple lymphadenopathy. Talaromyces marneffei was isolated in the initial blood cultures. As the fever persisted despite clearance of fungemia and 10 days of liposomal amphotericin B treatment, cervical lymph node fine-needle aspiration was performed. Mycobacterium intracellulare was isolated from sputum and neck node aspiration cultures. The patient was successfully treated with liposomal amphotericin B, clarithromycin, and ethambutol in addition to antiretroviral therapy. This case suggests that we should consider coinfection of opportunistic pathogens in febrile immunosuppressed patients if the patient does not respond properly to the initial treatment.